Treatment of the common cold with herbs used in Ayurveda and Jamu: monograph review and the science of ginger, liquorice, turmeric and peppermint - Retno S Wardani; Natalie Schellack; Tamlyn Govender; Abhay N Dhulap; Prapti Utami; Vinod Malve; Yong Chiat Wong (BioExcel Publishing Ltd, 2023)
Background: The common cold is typically managed with decongestants, antihistamines, antitussives and antipyretics. In addition to these established medications, herbal ingredients have been used over centuries to help treat common cold symptoms. The Ayurveda and Jamu systems of medicine, originating from India and Indonesia, respectively, have leveraged herbal therapies to treat many illnesses. Method: An expert roundtable discussion comprising specialists in Ayurveda, Jamu, pharmacology and surgery along with a literature review was conducted to evaluate the use of four herbs - ginger, liquorice, turmeric and peppermint - for common cold symptom management in Ayurvedic texts, Jamu publications and monographs from the World Health Organization, Health Canada and various European guidelines. Discussion: Due to a lack of antivirals, common cold management revolves around maintaining personal hygiene and symptom management. Herbal medicines have been an integral part of many cultures worldwide. Despite its growing acceptance, there is a perception that healthcare providers lack interest and may prevent patients from discussing the use of herbal medicines. Limited education and training may also widen the communication gap between patients and healthcare providers, hindering effective management. Conclusion: Evaluation of scientific evidence and the standing in international monographs can offer perspectives on the use of herbal medicines for common cold management.